Effects of supplementary lighting on various physiological processes and performance of chinese kale (Brassica oleracea L.) grown on different tiers of L-frame structure - Shakri, Nur Alyani (2018)
Vertical farming is an advanced level of agricultural technology practiced when agricultural land is less available, where plants are grown in vertically stacked or inclined layers and/or integrated in other structures. Vertical farming would have different growth performances at every tier position, associated with differences in light availability. Incorporating artificial light within vertical farming would give greater impact on the growth of plants. The present study was conducted to evaluate the effect of artificial light regimes using light-emitting diode (LED) on growth and physiological processes, yield and quality parameters of two Chinese kale (Brassica oleracea) varieties (Type B Curly Leaf and Hong Kong Chinese Kale) grown on five descending tiers (Tier 1, 2, 3, 4 and 5) of vertical L-frame structures. In the first experiment, plants grown on Tier 1 or upper most tier produced the highest fresh weight, leaf area, canopy diameter, plant height, number of leaves, root length and stem diameter compared to those grown on lower tiers (Tier 2, 3, 4 and 5). Type B Curly Leaf Chinese kale had higher fresh weight and total leaf area compared to Hong Kong Chinese kale. The interaction effect of combination between upper tier positions and Chinese kale variety Type B Curly Leaf showed significantly higher stem diameter and total leaf area. Fresh weight of Type B Curly Leaf Chinese kale on Tier 2 was significantly the highest. In the second experiment, growth of Type B Curly Leaf Chinese kale grown under different light regimes and different tier positions of L-frame structure was observed. The four different light regimes were L1: 12 hours daylight condition (1180 μmol m⁻²s⁻¹), L2: 12 hours daylight (1180 μmol m⁻²s⁻¹) with 3 hours LED light at night time (228 μmol m⁻²s⁻¹), L3:12 hours daylight (1180 μmol m⁻²s⁻¹) with 6 hours LED light at night time (228 μmol m⁻²s⁻¹) and L4: 12 hours LED light (1170 μmol m⁻²s⁻¹) on daytime. Plants grown in L4 light regime on day time resulted in higher number of leaves, canopy diameter, root length, fresh weight, total leaf area, chlorophyll content and vegetable firmness at different tier positions. Plants grown under L4 light regime and Tier 1 showed significant positive effects on most parameters. For the contrast analysis resulted shows that the Chinese kale grown under light regimes L1 was different from light regime L4 at the most parameters. The result also indicate that contrast analysis for the light regimes L2 and L3 which is supplementary light at night was different from light regimes L4 which is the better light regimes than others and more efficient in this study. In conclusion, growth and physiological processes of kale were significantly affected when grown under different light regimes and tier positions. The 12-hour LED light on day time had significant impact on plants grown on the vertical L-frame structure. The study proposes the use of LED lights to overcome low growth performance of Chinese kale on lower tiers to reduce the effect of shading in vertical structure. Plants exposed to natural light on upper tier position and receiving supplemental LED light on day time would yield positively on plant productivity and quality.